Effects of Corn Oil Supplementation on Gonad Maturation, Gonadosomatic Index, And Fecundity in Silver Rasbora (Rasbora Argyrotaenia) - Elsa R. A. Audina; Farida Mauludia; Akhmad T. Mukti; Nur Rohmah Heny Handayani (Journal of Aquaculture Science, 2026)
A 42-day experiment was conducted to determine the effects of corn oil supplementation on gonadal maturity, gonadosomatic index, and fertility in Rasbora argyrotenia broodstock. The experiment used a completely randomized design with three treatments and five replicates. The doses administered were: Treatment 1 (T1): 20 mL/kg of feed, Treatment 2 (T2): 25 mL/kg of feed, and Treatment 3 (T3): 30 mL/kg of feed. Fish (6.87 ± 0.42 cm) were reared in 25-liter aquariums at a density of 1 fish per liter. Supplementation of corn oil at a dose of 30 mL/kg of feed showed significant effects on gonadal maturity (70% reached stage IV), gonadosomatic index (11.58 ± 2.57), and fecundity (998.39 ± 9.06 eggs). Higher doses of corn oil were directly proportional to the gonadosomatic index and the number of eggs produced by R. argyrotaenia broodstock. The supplementation of corn oil in the diet significantly improved the reproductive performance of the wader pari fish, making it a viable nutritional strategy to optimize the production of R. argyrotaenia.